2019
DOI: 10.1186/s12937-019-0511-x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the low carbohydrate diet and the risk of breast Cancer in Iran

Abstract: BackgroundPrevious studies on the link between macronutrients and breast cancer have mostly focused on individual macronutrients rather than their combination. This study investigates the association between adherence to a low carbohydrate diet and odds of breast cancer among women.MethodsThis hospital-based case-control study was carried out on 412 women with pathologically confirmed breast cancer within the past year and 456 apparently healthy controls that were matched in terms of age and residential place.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…Previous validation study of DHQ in this population revealed good correlation coefficients between nutrients assessed by DHQ and multiple 24-h recalls completed over a year [35]. Deattenuated spearman correlation coefficients of equal or greater than 0.5 were obtained for energy, carbohydrate, protein, fiber, vitamin A, carotene, niacin, folate, vitamin B12, biotin, vitamin C, sodium, magnesium, iron, zinc, selenium between DHQ and the average of 24-h dietary recalls [40].…”
Section: Assessment Of Dietary Intakesmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous validation study of DHQ in this population revealed good correlation coefficients between nutrients assessed by DHQ and multiple 24-h recalls completed over a year [35]. Deattenuated spearman correlation coefficients of equal or greater than 0.5 were obtained for energy, carbohydrate, protein, fiber, vitamin A, carotene, niacin, folate, vitamin B12, biotin, vitamin C, sodium, magnesium, iron, zinc, selenium between DHQ and the average of 24-h dietary recalls [40].…”
Section: Assessment Of Dietary Intakesmentioning
confidence: 67%
“…We used a validated 146-item Diet History Questionnaire (DHQ) to assess participants' dietary intakes. A detailed description of DHQ, its development and validity has been explained in details elsewhere [35]. Briefly, it included 146 questions related to the past 12-month consumption of foods and Iranian mixed dishes.…”
Section: Assessment Of Dietary Intakesmentioning
confidence: 99%
“…Subjects who didn't answer to more than 70 items of the FFQ (n=25, 9 patients and 25 controls) were excluded. Further description of this study is reported elsewhere [29].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies were performed regarding relation between LCD and risk of chronic disease such metabolic syndrome [12,24,25], diabetes [19,26], cardiovascular disease [20,27], and cancer [28,29]. Nevertheless, a few studies especially large scale studies have been evaluated association between LCD and psychological disorders and their findings were inconsistence [23,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%